Making the 'reserve army' invisible: Lengthy parental leave and women's economic marginalisation in Hungary. Issue 4 (November 2014) - Fodor, Eva; Kispeter, Erika
Generous parental leave policies are popular in a number of countries around the world and are usually seen as a sign of the 'family friendliness' of the state. Relying on in-depth interviews with mothers on parental leave in Hungary, the authors argue that the context in which the policies are implemented should be examined when evaluating their consequences. In semi-peripheral, resource-poor Hungary lengthy parental leave policies turn women into an invisible 'reserve army of labourers'. While their employment is mostly unaccounted for in aggregate statistics, and political discourse suggests that their 'job' is to look after children, nevertheless many women do end up doing some work for wages during the almost five years they spend on parental leave. However, given the rigidity of the labour market and rampant discrimination against mothers with small children, their chances of obtaining formal employment are small. They therefore resort to doing ad hoc, temporary, informal work, which is often underpaid and well below their qualifications. Thus generous family policies do not necessarily indicate the 'women friendliness' of the state and may not lead to the relatively favourable trade-off between stable public sector work and lower wages suggested recently by comparative researchers. Instead, in this specific context, which combines legacies of state socialism, a backlash against women's emancipation before 1990 and a peripheral, vulnerable labour market, familialist policies are associated with a high degree of marginalisation for women with small children in which the state is at best complicit, at worst, an active agent.